Immunological Drivers in Graves' Disease: NK Cells as a Master Switcher - Gallo, Daniela; Piantanida, Eliana; Gallazzi, Matteo; Bartalena, Luigi; Tanda, Maria Laura; Bruno, Antonino; Mortara, Lorenzo (Frontiers in Endocrinology, 2020)
Graves’ disease (GD) is a common autoimmune cause of hyperthyroidism, which is eventually related to the generation of IgG antibodies stimulating the thyrotropin receptor. Clinical manifestations of the disease reflect hyperstimulation of the gland, causing thyrocyte hyperplasia (goiter) and excessive thyroid hormone synthesis (hyperthyroidism). The above clinical manifestations are preceded by still partially unraveled pathogenic actions governed by the induction of aberrant phenotype/functions of immune cells. In this review article we investigated the potential contribution of natural killer (NK) cells, based on literature analysis, to discuss the bidirectional interplay with thyroid hormones (TH) in GD progression. We analyzed cellular and molecular NK-cell associated mechanisms potentially impacting on GD in a view of identification of the main NK-cell subset with highest immunoregulatory role.